Disruptive behaviors and its impact on school performance: Case study - Valencia-Castro, Fatima Acnabel; Zambrano-Gómez, María Gabriela; Moreira-Castro, Silvia Alexandra; Alcívar-Intriago, Andrés Aladino; Aveiga-Alcívar, Cindy Lissette (International research journal of management, IT and social sciences, 2024)
The research was related to disruptive behaviors and their impact on academic performance. Its objective was to identify disruptive behaviors and their impact on academic performance in BGU students from the “Aida Coloma de Sánchez” Educational Unit in the province of Guayas. To this end, the research had a qualitative, quantitative and descriptive approach to generate information based on the results obtained during the implementation of the EFECO questionnaire to the students. This questionnaire was built with 39 items that allowed the evaluation of executive functions such as: emotional control, monitoring, organization of materials, initiative, and working memory. Some results indicate that at the level of the monitoring dimension raised, an average of 1.88 students were able to indicate that they always require help, regularly an average of 1.22 students, sometimes an average of 1.88 students, Very rarely an average of 2.44 and Never an average of 2.44 students. Finally, conclusions are presented which show that a minority segment of students require help in the different dimensions raised.